1998
DOI: 10.1093/hmg/7.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Impaired interaction of naturally occurring mutant NF2 protein with actin-based cytoskeleton and membrane

Abstract: Although schwannomin, the product of the neurofibromatosis type 2 gene, shares homology with three cytoskeleton-to-membrane protein linkers defining the ERM family, the mechanism by which it exerts a tumor suppressive activity remains elusive. Based on the knowledge of naturally occurring mutations, a functional study of schwannomin was initiated. Constructs encoding the two wild-type isoforms and nine mutant forms were transfected into HeLa cells. Transiently expressed wild-type isoforms were both observed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 32 publications
2
43
0
4
Order By: Relevance
“…The first 50 amino acids of merlin are required for the binding of merlin to CD44 and for inhibition of the CD44-HA interaction Studies have shown that merlin mutants lacking different portions of the NH 2 -terminal ERM-homology domain lose their ability to interact with the plasma membrane (Deguen et al, 1998;Koga et al, 1998), a finding that is consistent with the possibility that merlin engages CD44 using the segment(s) located in its NH 2 -terminal half. To define the domain of merlin that is required for its inhibitory effect on the CD44-HA interaction, we established five mutants each of which bore a 50-amino acid deletion within the first 250 residues of the NH 2 -terminal portion of merlin.…”
Section: Increased Expression Of Merlin Inhibits the Binding Of Fluormentioning
confidence: 62%
See 3 more Smart Citations
“…The first 50 amino acids of merlin are required for the binding of merlin to CD44 and for inhibition of the CD44-HA interaction Studies have shown that merlin mutants lacking different portions of the NH 2 -terminal ERM-homology domain lose their ability to interact with the plasma membrane (Deguen et al, 1998;Koga et al, 1998), a finding that is consistent with the possibility that merlin engages CD44 using the segment(s) located in its NH 2 -terminal half. To define the domain of merlin that is required for its inhibitory effect on the CD44-HA interaction, we established five mutants each of which bore a 50-amino acid deletion within the first 250 residues of the NH 2 -terminal portion of merlin.…”
Section: Increased Expression Of Merlin Inhibits the Binding Of Fluormentioning
confidence: 62%
“…These mutants are often associated with a more severe clinical outcome (Merel et al, 1995;Parry et al, 1996;Ruttledge et al, 1996;Deguen et al, 1998;Evans et al, 1998;Koga et al, 1998). It is widely held that tumor-suppressor mutants often act in a dominant-negative fashion to promote tumorigenesis (Nigro et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, mutants with an intact carboxy-terminal domain but with a deleted or altered amino-terminal domain are delocalized mainly in the perinuclear cytoplasmic region. Such delocalization was observed for a mutant protein modeled from naturally occurring mutations in which exons 2-3 are spliced out without frameshift, Sch-⌬(39-121) (Deguen et al 1998).…”
mentioning
confidence: 83%